The Anticancer Effect of a Flavonoid-Rich Extract of Bergamot Juice in THP-1 Cells Engages the SIRT2/AKT/p53 Pathway - Alessandro Maugeri; Caterina Russo; Laura Musumeci; Giovanni Enrico Lombardo; Giovambattista De Sarro; Davide Barreca; Santa Cirmi; Michele Navarra (MDPI AG, 2022)
Novel targets are constantly sought to fight hematologic malignancies. In this regard, high levels of SIRT2 expression are associated with unfavorable prognosis of acute myeloid leukemia. The interest in the plant kingdom has allowed the identification of ever-new anti-leukemic agents. Citrus × bergamia (bergamot) was proved to possess anticancer properties, yet no evidence is available regarding leukemia. For the first time, we studied the potential anti-leukemic effect of a flavonoid-rich extract of bergamot juice (BJe) in THP-1 cells, investigating the underlying mechanisms. Our findings showed that BJe reduced THP-1 cell proliferation, without affecting that of primary PBMCs, blocking the cell cycle in S phase and inducing apoptosis. Triggering of both extrinsic and intrinsic apoptotic pathways was witnessed by cleavage of caspase-8 and -9, which in turn activated caspase-3 and PARP. Interestingly, the increased p53 acetylation in THP-1 cells underlies SIRT2 inhibition by BJe, that was proved also in the isolated enzyme. Moreover, BJe hampered SIRT2 also by lowering its gene expression. Finally, BJe reduced AKT phosphorylation, which we hypothesized being the joining link between SIRT2 and p53, that play a pivotal role in BJe-induced cell cycle arrest and apoptosis in THP-1 cells. Our results suggest BJe as a potential anti-leukemic agent, via targeting of the SIRT2/AKT/p53 pathway.